INVESTIGATIONS OF SURFACES OF ATMOSPHERE LESS BODIES USING SCATTERED SOLAR LIGHT - Prokofjeva-Mikhailovskaja, V. V.; Rublevskij, A. N. (Одеські астрономічні публікації, 2017)
Sunlight scattered by surfaces of atmosphere less bodies carry information about details of these surfaces. Burns and Tedesco in 1979 published formula for estimations of dimensions of details located on surfaces of asteroids. Authors of this paper show that using of frequency methods for analysing of light curves or curves of colour index allows receiving of optimal information. Experiments confirm this statement. Estimations of dimensions of details located on the surface of the asteroid 1620 Geographos are in good agreements with facts receiving with radar observations. Analysis of synthetic colour indexes B-V and V-R of the asteroid 4 Vesta show estimations of dimensions of colour spots on its surface in the interval 660-9 km. Conclusion are made that investigations of high frequency modulations of light curves or curves of colour indexes of asteroids allow us to receive information about dimensions of details on its surfaces.